Langerhans cell histiocytosis - D R Aruna; G Pushpalatha; Sushma Galgali; Prashanthy (Wolters Kluwer Medknow Publications, 2011)
Langerhans cell histiocytosis (LCH) is a group of rare disorders histologically characterized by the proliferation of Langerhans cells. Multiple organs and systems may be involved by the disease. Typically, there is bone involvement and, less frequently, lesions may be found in the lungs, liver, lymph nodes, skin, and mucosa. Oral soft tissue lesions without bone involvement are rare. We present a case of oral lesions associated with LCH in a young woman.